Integrated approach: Moving towards innovative teaching / Siti Khalijah Majid and Rahimah Abd. Wahab - Majid, Siti Khalijah; Abd. Wahab, Rahimah (2009)
One of the goals of an academic institution is to produce graduates who are able to fulfill the needs of potential employers. This, however, will not be realised if graduates are not able to apply skills learnt in the classroom to the workplace. It has been found that even in the classroom, many students are not able to apply skills learnt in one course to another even though they are inter-related. For example, English language skills learnt are not applied to the other non-language classes. Hence, this paper suggests that integration across disciplines be implemented as one of the ways towards a more holistic approach in educating our students. It also explores the benefits of integration and suggests several integration techniques that can be applied to the Faculty of Office Management and Technology (FOMT) in UiTM Pahang.